Fast and robust object-extraction framework for object-based streaming system. (14th February 2008) - Ahmad, Ashraf M.A.; Lee, Suh-Yin
Video streaming poses significant technical challenges in the quality of service guarantee and efficient resource management. In this paper, we propose an efficient moving object-extraction algorithm suitable for real-time content-based multimedia streaming systems. A motion vector based object extraction is used to dynamically detect the objects. To utilise the bandwidth efficiently, the video objects can be detected in real time, encoded, and transmitted with higher quality and a higher frame rate than those in the background. To meet the real-time requirement, no computationally intensive operation is included in this framework. Moreover, to guarantee the highest speed, the entire implementation is operating in the compressed domain without any need for decompression.